2017
DOI: 10.1002/zoo.21355
|View full text |Cite
|
Sign up to set email alerts
|

Environmental changes and anthropogenic factors modulate social play in captive bottlenose dolphins (Tursiops truncatus)

Abstract: Social play varies among species and individuals and changes in frequency and duration during ontogeny. This type of play is modulated by environmental changes (e.g., resource availability). In captivity, cetaceans and their environment are managed by humans, and training sessions and/or public presentations punctuate the day as well as other frequent or occasional events. There is a lack of research on the effects of environmental events that occur in captivity and might affect dolphins' behavior. We studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 84 publications
(96 reference statements)
3
37
2
Order By: Relevance
“…Stepwise logistic regression models of those behaviors exhibited by squirrels that were significantly related to visitor numbers (both number of adults and number of children) in the forced entry models shown in Table 2 Behavior the pre-existing animal-keeper relationship seems to influence squirrel behavior around other adults. Ward and Melfi (2015) have previously found that change in behavior can be driven by keeper-animal relationships. This would be an interesting area for future study in other species; it might also be interesting to compare visitor interaction levels between individuals that have been hand reared with those that had not.…”
Section: Tablementioning
confidence: 99%
“…Stepwise logistic regression models of those behaviors exhibited by squirrels that were significantly related to visitor numbers (both number of adults and number of children) in the forced entry models shown in Table 2 Behavior the pre-existing animal-keeper relationship seems to influence squirrel behavior around other adults. Ward and Melfi (2015) have previously found that change in behavior can be driven by keeper-animal relationships. This would be an interesting area for future study in other species; it might also be interesting to compare visitor interaction levels between individuals that have been hand reared with those that had not.…”
Section: Tablementioning
confidence: 99%
“…Most social activities of four BDs (Tursiops aduncus) were shown to be globally more frequent in the early afternoon [65]. However, it has been shown that captive odontocetes were less active in the afternoon [17,66]. A higher rate of social interactions in the morning and at noon for YFPs and BDs, as well as the higher rate of pectoral fin contacts and body contacts that are often displayed during social interactions such as swimming in contact, socio-sexual interactions or social play, could be due to this higher activity level.…”
Section: Time Of the Daymentioning
confidence: 94%
“…Among social behaviors, social interactions, such as agonistic interactions and social play, were suggested to be potential indicators of welfare in bottlenose dolphins [16,17]. Social play is thought to reflect positive welfare because it has been described as occurring only when an individual's primary needs are fulfilled [18,19], but the fact that play can evolve into agonistic interactions implies the need to use this parameter with caution [20].…”
Section: Introductionmentioning
confidence: 99%
“…Research on whether the benefits of cetacean captivity are outweighed by animal welfare concerns is also in contention. Some research has concluded that animal behaviour can be normal and welfare high when provided with adequate enrichment; recent research has shown that dolphins positively anticipate interacting with their trainers ( Perelberg et al, 2010 ; Tizzi, Accorsi & Azzali, 2010 ; Clegg, Borger-Turner & Eskelinen, 2015 ; Clegg, Van Elk & Delfour, 2017 ; Serres & Delfour, 2017 ; Makecha & Highfill, 2018 ; Clegg et al, 2018 ). Yet animals in captivity have also been found to have increased stress levels, poor diet, a higher chance of injury, and, in the case of killer whales, higher mortality rates in captivity ( Kyngdon, Minot & Stafford, 2003 ; Whale and Dolphin Conservation Society & The Humane Society of the United States, 2003 ; Ugaz et al, 2013 ; Lott & Williamson, 2017 ; Jett & Ventre, 2015 ).…”
Section: Introductionmentioning
confidence: 99%